Food labeling politics and policies in the United States - Thomas, Courtney Irene Powell; Oliver, Joshua (Common Ground Research Networks, 2020)
"What is included on food labels and what is excluded? What are the criteria for "organic" foods and who determines that those criteria have been met? Do nutrition panels effectively communicate information to consumers? What is the difference between "free range" and "cage free," and which should one buy if he or she loves eggs and chickens? When a product is labeled as "gluten free," has there been some kind of certification process, and who can be held accountable if someone dies after eating inaccurately labeled food? Those questions are the impetus for this book, which delves into related research to find those answers and what those answers mean to the U.S. at large"--